The Mediating Roles of Emotional Regulation on Negative Emotion and Internet Addiction Among Chinese Adolescents From a Development Perspective - Liang, Lijuan; Zhu, Mingrui; Dai, Jiali; Li, Min; Zheng, Ya (Frontiers in Psychiatry, 2021)
Previous researches indicated that emotional regulation can be associated with depression and anxiety, which may be an important mediating factor between emotional regulation and internet addiction. However, the mechanism between these associations has received little attention and it is still unclear. This study has examined 716 Chinese adolescents, 341 were males (47.6%), aged 13 to 18(Mean = 14.58, SD = 1.50), using a cross-sectional survey involving Young's Diagnostic Questionnaire for Internet Addiction, the nine-item Patient Health Questionnaire (PHQ-9), the seven-item Generalized Anxiety (GAD-7) scale, and the Emotion Regulation Questionnaire (ERQ). Correlation analysis, multiple-group analysis and structural equation modeling were carried out in SPSS Statistics version 23 (IBM, Armonk, NY) and AMOS version 21. Cognitive reappraisal had a significantly negative direct effect on Internet addiction (β = −0.118, p < 0.05). Furthermore, negative emotions mediated the relationships between expression suppression and Internet addiction [β = 0.149, 95% CI = (0.099, 0.212)] and the relationship between cognitive reappraisal and Internet addiction [β = −0.101, 95% CI = (−0.147, −0.065)]. The differences in the structure path coefficients for different development stages demonstrated that recognitive reappraisal showed more protective roles for negative emotion (p < 0.01), and negative emotion also predict Internet addiction more effectively in high school students (p < 0.001). However, cognitive reappraisal directly predicted negative Internet addiction in junior high school students. Therefore, the intervention on adolescents for internet addiction should not only focus on emotional regulation and negative emotion, but also development stages of adolescents.